Emerging Trends in Human Resource Management and Education in Indonesia (2018-2023): A Bibliometric Analysis - Suharyanto Suharyanto (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This article presents a bibliometric analysis of emerging trends in Human Resource Management (HRM) and its intersection with education in Indonesia over the period 2018 to 2023. Employing bibliometric methodology, this study measures and analyzes scientific literature related to HRM, with a specific focus on educational settings and the impact of educational advancements on HRM practices. The research data was sourced from various academic publications, including journals, conference papers, and other HRM-related publications, with a particular emphasis on the educational sector. The bibliometric analysis, conducted using specialized software such as Biblioshiny, facilitated the generation of thematic maps and citation matrices, offering insights into the evolving dynamics at the confluence of HRM and education. The results of this analysis provide a comprehensive understanding of recent changes and trends in HRM practices within the Indonesian educational context, encompassing themes such as HRM strategies in educational institutions, the role of technology in HR education, sustainability in educational HRM, and the challenges of managing human resources in the dynamic environment of educational settings. This article contributes significantly to the understanding of HRM in the context of Indonesian education and offers valuable guidance for practitioners, academics, and policymakers in navigating the complexities of HRM challenges in educational environments.